Validating the factors of the English and Filipino versions of the sense of self scale - Ganotice, Fraide A. Jr; Bernardo, Allan B.I (Philippine journal of psychology, 2010)
"The Sense of Self (SOS) scale measures different aspects of a learner's sense of purpose and self-concept that are related to their motivations to strive in their academic endeavors, and is designed to have four dimensions: sense of purpose, sense of reliance, negative self-esteem, and positive self-esteem."